الغزل العذري عند الشواعر عبر العصورPlatonic Spinning of Poetry through the Ages (Al-Qamar, 2021)
The platonic spinning is characterized by purity, chastity, transcendence in feelings, and great spiritual strength, but this life does not eliminate the woman as the second party in the experience of love, because this condemns the experience to perversion. The spinning is represented in three: the platonic spinning, the sensual or physical spinning, then the mystical spinning which expresses love towards the divine self. In this work the use of platonic spinning in different ages of poetry has been discussed. Moreover, the fact that how different categories of platonic spinning have added a magical essence in poetry, has also been under consideration.
Keywords: Platonic spinning; poetry; purity; woman; love